Business Analytics Toolkit for Tech Hubs : Lessons Learned from infoDev's mLabs and mHubs - World Bank Group (World Bank, Washington, DC, 2016)
This toolkit, commissioned by infoDev, a global partnership program within the World Bank, provides guidance on how to develop business analytics, measuring and learning from the performance and effects of mobile application labs (mLabs) and mobile social networking hubs (mHubs). It was made for managers of tech hubs. Dozens of tech hubs have emerged over the last few years across the globe. Managers of these innovation and entrepreneurship enablers grapple with problems that infoDev has experience with. This toolkit takes lessons that infoDev has gathered from its own tech hub pilots, mLabs and mHubs, and apply them to tech hubs in general. The toolkit is especially useful for current and future mLab and mHub managers. mLabs and mHubs are tech hubs established through grants administered by the infoDev Digital Entrepreneurship Program. infoDev is committed to supporting the analytical capacities of mLabs and mHubs. This toolkit is part of that agenda. It will help grantees to improve local implementation while setting a common framework on how to collaborate with infoDev on business analytics and performance measurements. The third target audience is mobile innovation specialists at other World Bank units and other development organizations, who design impact and measurement frameworks for tech hubs. Given the recent rise in numbers of tech hubs, international development organizations are exploring if and how they can be employed to achieve socio-economic development impact goals. In particular, tech hubs’ flexibility and diverse potential effects have sparked interest but have also caused problems for specific and concrete analysis and projection of hubs’ effects and impact. This toolkit addresses this complication. All elements of the toolkit that speak of infoDev’s role in facilitating and coordinating with mLabs or mHubs on business analytics processes can be seen as use cases with potential for replication and adaptation by practitioners and decision makers of other development organizations, including relevant units of the World Bank.